PERUBAHAN MUTU FISIK DAN MUTU KIMIA KEDELAI SELAMA PENYIMPANAN - Ratna Wilis Arief; Robet Asnawi (Jurnal WACANA PERTANIAN, 2019)
Soybean is one of the leguminous plants and is the main source of protein and vegetable oil in the world. Soybean is the most important strategic main food crop after rice and corn. Caused of their high protein and fat content, soybean seeds have fast decreased quality during storage, both for consumption material and as a source of seeds. This study aims to determine changes in physical and chemical quality of several soybean varieties during storage. This research was conducted from February to August 2016 in the Agricultural Science Park (TSP) Natar. The study was conducted in a Randomized Block Design (RBD) with three replications. This study uses 4 soybean varieties, namely: Grobogan, Burangrang, Anjasmoro, and Argomulyo; packaged using polyethylene plastic bags (PE) 0.8 mm. Observation parameters included physical quality (split grains, broken grains, other colored grains, wrinkled grains, and impurities), hardness and chemical quality (moisture content, ash content, protein content, fat content, crude fiber content, and carbohydrate content). The observations showed that: Anjasmoro variety has the best physical quality (Quality I) compared to other varieties, both before storage (0 months), and after storage (6 months); There was increased water content, protein content, ash content, and crude fiber content, but a decrease in carbohydrate content in soybean seeds after storage for 6 months, while the ash content did not change significantly;There was increased the level of hardness of soybean seeds during storage for 4 soybean varieties that were used around 3,68% - 8,33%.